Perancangan Sosial Media Sebagai Media Kampanye Persuasi Untuk Menghidupkan Kembali Permainan Tradisional di Surabaya pada Era Digital - Aisya Jasmine Defina; Bayu Setiawan; Pungky Febi Arifianto (Pusat Riset dan Inovasi Nasional, 2025)
This study aims to design a social media campaign that encourages children to play traditional games through the involvement of parents, with the goal of preserving traditional games in the digital era. The methods used include qualitative and quantitative approaches, such as interviews, observations, and data analysis to determine the effective communication strategy. This campaign will use Instagram as the primary platform, with four content pillars: Awareness, Education, Engagement, and Persuasion. The Awareness pillar focuses on reintroducing traditional games, Education provides information about the benefits and cultural values, Engagement encourages active participation, and Persuasion invites the audience to join events that support the preservation of traditional games. The results show that the use of social media, particularly Instagram, is effective in attracting the attention of parents and children, raising awareness about the importance of traditional games in supporting children's physical, social, and emotional development, as well as preserving Indonesia's cultural heritage amidst the advancement of digital technology.